MENGETAHUI NILAI KEKERASAN DAN STRUKTUR MIKRO DARI BAHAN BAJA PEGAS DAUN AKIBAT PERLAKUAN PANAS DENGAN TEMPERATURE DAN PENDINGIN YANG BERVARIASI - Firda Herlina; M. Firman; Edi Yani Fazri (Universitas Lambung Mangkurat, 2015)
One study on the effect of heating temperature, duration of heating and rapid cooling of the properties of hardness and microstructure of the steel hypoeutectoid. The study used a variation of heating temperature 780 ° C, 830 ° C, and 880 ° C with long holding time 2, 4 and 6 minutes, without any further heat treatment such as tempering. The maximum hardness value obtained is 62.7 HRC.This research was conducted in February 2015 through to completion. The research was carried out in several places that the sample preparation is done at home, while the hardness and microstructure test done at the Laboratory of Mechanical Engineering Uniska Banjarmasin, research methods were conducted in this study to prepare materials, Prepare samples is 35x30 mm, heat treatment is temperature of 400 ° C, 500 ° C and 600 ° , hardness test method brinell, and test microstructure.Research shows Effect of temperature variations with different cooling media for violence leaf spring steel used is, to the best hardness value of the heating temperature of 400 ° C, 500 ° C and 600 ° C is at a temperature of 400 ° C with a cooling medium used is air which its average value is 272.2 HB from 252.8 HB to the average raw material and Influence of temperature variations with different cooling media on microstructure of steel leaf springs are used, namely, to the best hardness from the heating temperature of 400 ° C, 500 ° C and 600 ° C is at a temperature of 400 ° C with air cooling medium in which the average value of 13% pearlite and ferrite average value of 87 % of the average raw material and ferrite 10.43% pearlite 89.57%,Keywords: Hardness, Steel, Temperature, Cooling